ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR TINGKAT PROFITABILITAS PADA PT. PLN (PERSERO) AREA MAKASSAR - Astuty Hasti (AkMen JURNAL ILMIAH, 2015)
Technological development increasing rapidly caused the need for expertise in analyzing financial statements. Therefore the company is required to select the information in the vast network to determine the current condition of the company and the estimates of future conditions. Analyze financial statement can help the parties interested in selecting and evaluating information and just focus with such information, so that each company is required to improve its competitiveness by encouraging each company to improve the quality of both the quality of services and quality of products. But in fact, virtually all companies experience the same problem, namely how to allocate their resources effectively and efficiently in order to achieve company goals is to obtain the maximum profit to maintain the existence of company.